i-Soft Separation Axioms in Soft Topological Spaces - Sabih W. Askandar; Amir A. Mohammed (Tikrit Journal of Pure Science, 2020)
In the current study the researchers  have been introduced a modern kind of soft separation axioms which is named i-soft separation axioms by using the concept of soft i-open sets [17] in soft topological spaces, the relations among i-soft separation axioms and many examples about it are investigated. Further, they found that soft separation axioms imply i-soft separation axioms, but, the converses may not be true. Also, many theorems have been proved which are clarified the properties of i-soft separation axioms